ANALISIS SUBJEK KOLEKSI PERPUSTAKAAN DI UPT PERPUSTAKAAN UNIVERSITAS LANCANG KUNING - Bella Bintari; Rismayeti Rismayeti; Hadira Latiar (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
The title of this research is the analysis of the subject of library collections at the Technical Implementation Unit (UPT) of the Lancang Kuning University Library. The purpose of this study was to determine how the subject analysis in the Technical Implementation Unit (UPT) Lancang Kuning University Library. The method used is descriptive quantitative, with a sample of 867 collection titles in the Technical Implementation Unit (UPT) of the Lancang Kuning University Library. Data collection techniques are observation, interviews, literature study, and documentation. The results showed that from a total of 867 collections, a small part (7%) of collection subjects were in accordance with the principle of determining the subject specifically and directly, then out of a total of 867 collection titles, a small part (7%) of collection subjects were in accordance with the usability principle, then from a total of 867 the title of the collection a small part (6%) of the subject of the collection is in accordance with the principle of uniformity, then from a total of 867 titles of the collection a small part (4%) of the subject of the collection is in accordance with the principle of subdivision of physical form, then from a total of 867 titles of the collection a small part (3%) of the subject of the collection in accordance with the principle of a specific topic or aspect, then out of a total of 867 collection titles, a small portion (1%) of the subject of the collection is in accordance with the principle of geographical subdivision, then the Technical Implementation Unit (UPT) of the Lancang Kuning University Library does not apply a collection of chronological subdivisions, further from a total of 84 the title of the collection there are 19 collections on the principle of biography a small part (23%) subj oak collections are in accordance with biographical principles, then out of a total of 175 collection titles there are 38 collections on the principles of language and literature, a small portion (22%) of collection subjects according to the principles of language and literature.